Physicians' Acceptance of Triage Guidelines in the Context of the COVID-19 Pandemic: A Qualitative Study - Merlo, Federica; Lepori, Mattia; Malacrida, Roberto; Albanese, Emiliano; Fadda, Marta (Frontiers in Public Health, 2021)
Aims: One of the major ethical challenges posed by the Covid-19 pandemic comes in the form of fair triage decisions for critically ill patients in situations where life-saving resources are limited. In Spring 2020, the Swiss Academy of Medical Sciences (SAMS) issued specific guidelines on triage for intensive-care treatment in the context of the Covid-19 pandemic. While evidence has shown that the capacities of intensive care medicine throughout Switzerland were sufficient to take care of all critically ill patients during the first wave of the outbreak, no evidence is available regarding the acceptance of these guidelines by ICU staff. The aim of this qualitative study was to explore the acceptance and perceived implementation of the SAMS guidelines among a sample of senior physicians involved in the care of Covid-19 patients in the Canton of Ticino. Specific objectives included capturing and describing physicians’ attitudes towards the guidelines, any challenges experienced in their application, and any perceived factors that facilitated or would facilitate their application. Methods: We conducted face-to-face and telephone interviews with a purposive sample of 9 senior physicians employed as either head of unity, deputy-head of unit, or medical director in either one of the two Covid-19 hospitals in the Canton of Ticino during the peak of the outbreak. Interviews were transcribed verbatim and thematically analyzed using an inductive approach. Results: We found that participants held different views regarding the nature of the guidelines, saw decisions on admission as a matter of collective responsibility, argued that decisions should be based on a medical futility principle rather than an age criterion, and found that difficulties to address end-of-life issues led to a comeback of paternalism. Conclusions: Results highlight the importance of clarifying the nature of the guidelines, establishing authority and responsibility during triaging decisions, recognizing and addressing sources of interference with patients’ autonomy, and the need of a cultural shift in timely and efficiently addressing end-of-life issues.